Pericardial rupture leading to cardiac herniation after blunt trauma. (June 2020) - Guenther, Timothy; Rinderknecht, Tanya; Phan, Ho; Wozniak, Curtis; Rodriguez, Victor
Abstract: Pericardial rupture with cardiac herniation is a rare traumatic injury with an estimated incidence of 0.37% after blunt trauma. Most commonly occurring after high-speed impact, such as in motor vehicle or motorcycle collisions, pericardial rupture is associated with a high mortality rate. Radiologic diagnosis can be challenging; cross-sectional imaging findings can be suggestive of pericardial rupture but are often non–specific, and echocardiography windows are often obscured. Definitive diagnosis is generally made intra-operatively. Treatment involves reduction of the heart into normal anatomic position with repair of the pericardium, either primarily or with a patch. Fewer than 60 cases of pericardial rupture from blunt trauma have been reported in the literature. We describe a 65 year old poly-trauma patient who sustained pericardial rupture with subsequent cardiac herniation with cardiovascular collapse, and we discuss the considerations and complexities of his successful repair.